Penerapan Teknologi Sistem Informasi dalam Monitoring Kinerja Aparat di Desa Marokota - Genofasius Aril Bobo; Yulius Nahak Tetik; Paulus Mikku Ate (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Information technology advancements have sparked a digital revolution in village government operations, especially in tracking and assessing village officials' performance. Performance evaluation is still done by hand in many village government organizations, which frequently causes reporting delays, ineffective data processing, and a lack of transparency in the evaluation process. In order to facilitate a more efficient and organized monitoring and performance evaluation process, an information system therefore required. In order to support the management village apparatus data, performance assessment procedures, and integrated reporting, this study intends design and develop a web-based monitoring system for assessing the performance village officials. To represent the system processes in an organized way, the system design is modeled using the Unified Modeling Language (UML), which includes use case diagrams, activity diagrams, and sequence diagrams. To make sure that every system function performs in accordance with user requirements, system testing is carried out using the Black Box Testing method. The findings demonstrate the system's ability handle village apparatus data, carry out automated performance evaluation procedures, compute final scores using assessment indicators, and produce precise performance reports. It is anticipated that the system's implementation will enhance the village officials' performance monitoring procedure's efficacy, efficiency, transparency, and structure.